Application of magnetic molecularly imprinted polymers for the solid phase extraction of selected nitroaromatic compounds from contaminated aqueous environments. Issue 3 (11th February 2017) - Tavengwa, Nikita Tawanda; Cukrowska, Ewa; Chimuka, Luke
ABSTRACT: Magnetic molecularly imprinted polymers (MIPs) were successfully synthesized by bulk polymerization for the extraction of nitroaromatic compounds (NACs). Based on the HPLC method, the linear calibration range of 0.5–5 mg L −1 for 2, 4-dinitrotoluene, nitrobenzene and 2-nitrotoluene gave detection limits of 13.6, 7.7 and 27.2 µg L −1, respectively, and good correlation values of R 2 > 0.993 of all the analytes were obtained. The optimum sorption was at a sorbent dosage of 5 g L −1, a contact time of 15 min and at pH 8. Recoveries for 2, 4-dinitrotoluene, nitrobenzene and 2-nitrotoluene from spiked real water samples were all 82%.